Biological effect of tissue plasminogen activator (t-PA) and DNase intrapleural delivery in pleural infection patients. Issue 1 (24th September 2019) - Kanellakis, Nikolaos I; Wrightson, John M; Hallifax, Rob; Bedawi, Eihab O; Mercer, Rachel; Hassan, Maged; Asciak, Rachelle; Hedley, Emma; Dobson, Melissa; Dong, Tao; Psallidas, Ioannis; Rahman, Najib M
Abstract : Background: Pleural infection (PI) is a major global disease with an increasing incidence, and pleural fluid (PF) drainage is essential for the successful treatment. The MIST2 study demonstrated that intrapleural administration of tissue plasminogen activator (t-PA) and DNase, or t-PA alone increased the volume of drained PF. Mouse model studies have suggested that the volume increase is due to the interaction of the pleura with the t-PA via the monocyte chemoattractant protein 1 (MCP-1) pathway. We designed a study to determine the time frame of drained PF volume induction on intrapleural delivery of t-PA±DNase in humans, and to test the hypothesis that the induction is mediated by the MCP-1 pathway. Methods: Data and samples from the MIST2 study were used (210 PI patients randomised to receive for 3 days either: t-PA and DNase, t-PA and placebo, DNase and placebo or double placebo). PF MCP-1 levels were measured by ELISA. One-way and two-way analysis of variance (ANOVA) with Tukey's post hoc tests were used to estimate statistical significance. Pearson's correlation coefficient was used to assess linear correlation. Results: Intrapleural administration of t-PA±DNase stimulated a statistically significant rise in the volume of drained PF during the treatment period (days 1–3). No significant difference was detected between any groups during the post-treatment period (days 5–7). Intrapleural administration of t-PA increased MCP-1 PF levels during treatment; however, no statistically significant difference was detected between patients who received t-PA and those who did not. PF MCP-1 expression was not correlated to the drug given nor the volume of drained PF. Conclusions: We conclude that the PF volume drainage increment seen with the administration of t-PA does not appear to act solely via activation of the MCP-1 pathway.